Could AGE/RAGE-Related Oxidative Homeostasis Dysregulation Enhance Susceptibility to Pathogenesis of Cardio-Metabolic Complications in Childhood Obesity? - Corica, Domenico; Aversa, Tommaso; Ruggeri, Rosaria Maddalena; Cristani, Mariateresa; Alibrandi, Angela; Pepe, Giorgia; De Luca, Filippo; Wasniewska, Malgorzata (Frontiers in Endocrinology, 2019)
Background Advanced glycation end-products (AGEs) and their cell receptor (RAGE) are involved in the pathophysiology of cardio-metabolic diseases. Interaction of AGEs with RAGE results in increased generation of oxygen radicals and pro-inflammatory cytokines. Circulating soluble RAGE (sRAGE) interacts with AGEs in order to counterbalance the negative effects of AGEs-RAGE interaction. Objectives To define factors influencing AGEs, sRAGE, AGEs/sRAGE-ratio and advanced oxidation-protein products (AOPPs) levels and to investigate changes in oxidative balance among overweight/obese children. Materials and methods Cross-sectional, one Center, case-control study included 41 overweight and obese children aged between 5–16 years and 36 lean matched controls. Inclusion criteria were: BMI ≥ 1 SD; term birth; no genetic or endocrine causes of obesity; no associated chronic diseases neither chronic therapies. All patients underwent clinical and biochemical investigations (lipid and glucose profiles, liver, renal and thyroid function tests, uric acid, C-reactive protein (CRP), AGEs, sRAGE and AOPPs serum concentrations). Significance was established at 0.050. Results AOPPs, AGEs/sRAGE-ratio, HOMA-IR, triglycerides, triglycerides/HDL-ratio, total cholesterol (TC)/HDL-ratio, atherogenic-index of plasma (AIP), uric acid, CRP were significantly higher, whereas sRAGE and HDL were significantly lower in overweight/obese children than controls. sRAGE was significantly negatively correlated with BMI SD, TC/HDL-ratio, CRP, AOPPs and positively with HDL. AGE/sRAGE-ratio and AOPPs were significantly positively correlated with BMI SD, TC/HDL-ratio, AIP, CRP, and negatively with HDL. BMI SD was independently associated with AGEs/sRAGE-ratio (B=0.06; p= 0.008), AOPPs (B=0.13; p=0.02) and sRAGE (B= -73.18; p=0.000). Conclusions We demonstrated, for the first time in a pediatric cohort, a significant higher value of AGEs/sRAGE-ratio among overweight/obese children, expression of a relative shift to oxidant from anti-oxidant factors, suggesting an AGE/RAGE-related oxidative homeostasis dysregulation that could enhance susceptibility to oxidative/inflammatory tissues damage. Severity of overweight, influencing the increase of oxidative stress in human organism and even in children, may contribute to the pathogenesis of long-term cardiovascular and metabolic alterations.